Real-world biologic treatment patterns and healthcare resource utilization in psoriasis patients using an insurance claims database in Japan - Celine Miyazaki; Junya Masuda; Mateo Delclaux Rodriguez-Rey; Marta Natalia Stelmaszuk; Jonatan Freilich; Phiona I-Ching Tsai; Hidehisa Saeki (Journal of Dermatological Treatment)
Background With advent of newer treatments for psoriasis, real-world use of biologics in Japan is evolving.Methods This retrospective study utilized data from patients with ≥1 psoriasis-related biologic claims record between January 2016 and December 2020 in Japan to evaluate treatment patterns, healthcare resource utilization (HCRU), and associated costs. Data were analyzed using descriptive statistics.Results Of 1,614 eligible patients, 72.5% were male, 29.2% had comorbid hypertension and 26.6% had comorbid cardiovascular disease. Interleukin (IL)-17 and tumor necrosis factor alpha (TNFα) inhibitors were commonly prescribed across lines of treatment, while IL-23 inhibitors were most considered for switches (92% of switches were from IL-12/23/IL-17/TNFα inhibitors). The overall mean adherence rate for all classes was 80.1%, but adherence varied across biologics. Infliximab and IL-23 inhibitor users exhibited optimal medical possession ratios, reflecting the best adherence rates. Overall HCRU (visits/patient-year) was 9.05 for outpatient visits, 0.09 for inpatient hospitalization, and 0.5 for psoriasis-related phototherapy. HCRU associated with hospitalization was slightly higher for bio-experienced patients and so was the overall costs per patient-year relative to bio-naïve patients.Conclusion Variable adherence rates observed suggest the need for improvement in treatment management with different biologics. Bio-experienced patients burdened by disease progression and treatment switches may result in increased HCRU.